2022
DOI: 10.1080/23144599.2022.2038494
|View full text |Cite
|
Sign up to set email alerts
|

Frequently used therapeutic antimicrobials and their resistance patterns on Staphylococcus aureus and Escherichia coli in mastitis affected lactating cows

Abstract: Mastitis is one of the most frequent and costly production diseases of dairy cattle. It is frequently treated with broad-spectrum antimicrobials. The objectives of this work were to investigate the prevalence of Staphylococcus aureus and Escherichia coli , find out the antimicrobials used in mastitis treatment, and explore the antimicrobial resistance profile including detection of resistance genes. Bacterial species and antimicrobial resistance genes were confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
2
8
2
Order By: Relevance
“…The target of SUL, and the basis for their selectivity, is the enzyme dihydropteroate synthase in the folic acid pathway [ 52 ]. Our study found that 26% and 30% of isolates carried sul 1 and sul 2 genes ( Table-5 ), which was supported by a study in Bangladesh with 47.1% and 32.4% abundance, respectively [ 51 ]. The resistance to β-lactam antibiotics in pathogens from livestock has been continuously reported in recent years [ 53 , 54 ], and predominantly ESBLs produced from E. coli are considered a key resistance mechanism [ 55 ].…”
Section: Antimicrobial Susceptibility Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The target of SUL, and the basis for their selectivity, is the enzyme dihydropteroate synthase in the folic acid pathway [ 52 ]. Our study found that 26% and 30% of isolates carried sul 1 and sul 2 genes ( Table-5 ), which was supported by a study in Bangladesh with 47.1% and 32.4% abundance, respectively [ 51 ]. The resistance to β-lactam antibiotics in pathogens from livestock has been continuously reported in recent years [ 53 , 54 ], and predominantly ESBLs produced from E. coli are considered a key resistance mechanism [ 55 ].…”
Section: Antimicrobial Susceptibility Resultssupporting
confidence: 86%
“…The antimicrobial resistance profile is helpful for understanding the pathogenesis of E. coli infection in bovine mastitis [ 49 ]. Some studies have shown that the tet A gene is more prevalent than the tet B gene in E. coli strains [ 11 , 44 , 50 , 51 ], and our results ( Table-5 ) were different with similar proportions in both tet A and tet B ( Figure-3 ). Our study revealed that six isolates that carried tet A were tetracycline-resistant, similar to the isolates that carried tet B, but none of the tetracycline-resistant isolates harbored both these genes.…”
Section: Antimicrobial Susceptibility Resultscontrasting
confidence: 53%
“…(45.20%) and Staphylococcus spp. (43.75%) and one-third of coliforms (31.57%) developed resistance to ampicillin, as observed in previous findings on Staphylococcus and coliforms [22,24], while contrasting with the findings of [13] regarding Streptococcus. Ampicillin intramammary ointment is highly accessible for mastitis treatments in Taiwan; therefore, bacteria are likely to develop resistance against ampicillin on dairy farms.…”
Section: Discussioncontrasting
confidence: 48%
“…showed a negative correlation between phenotypic and genotypic antimicrobial resistance to tetracycline; however, a previous study found a positive correlation in Staph. aureus [24].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding E. coli, the highest resistance was observed against oxacillin (64.71%) and ampicillin (58.82%) antibiotics. Oproxamitelly 30% of E. coli isolates were resistant to ceftriaxone, ciprofloxacin and cefaclor [ 60 ]. That supported the urgent need for exploring alternative antibacterial agents to avoid AMR phenomena.…”
Section: Discussionmentioning
confidence: 99%